PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Food and beverages yang terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2016) - Renaldi, Reza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims at determining the effect of working capital management on the companyâ€™s profitability. This quantitative research is an explanatory research which explains the relation or influence among variables. The independent variables are inventory conversion period, average collection period, payable deferral period and cash conversion cycle. The dependent variable of this study profitability that measured using Return on Asset (ROA).From population of 14 companies, 12 companies were selected as the sample through purposive sampling. This study uses secondary data in a form of annual financial report of Food and beverage companiesÂ from 2012 to 2016, which were obtained from the Indonesia Stock Exchane. The data then analyzed using Multiple Linear Regression analysis.The partial test of the research shows that inversion conversion period, account payable periode, and cash conversion cycle have a negative and significant relation with profitability. However, average collection period has a positife and significant relation with profitability (ROA).Keywords: Profitability, Cash Conversion Cycle, Inventory Conversion Period, Average Collection Period, Payable Defferal Period